In Search of the Context of a Question - Strandberg, Hugo Joakim (My University, 2020)
How is the role of context in moral philosophy to be understood? Why is the consideration of context important here? This paper is a small contribution to answering these questions. The kind of context that is in focus does not help us answer moral questions but is essential for understanding what kind of moral question arises – indeed, if any question arises at all. For whom does the question arise? What form does the question have for him or her? What relation does the person for whom it arises have to the events in the example as described by the philosopher? In considering such issues, the importance of thinking from an existentially and morally engaged perspective becomes evident.
Keywords: moral question; context; example; theatre; Haidt